2017
DOI: 10.18632/oncotarget.14730
|View full text |Cite
|
Sign up to set email alerts
|

SPECT and PET radiopharmaceuticals for molecular imaging of apoptosis: from bench to clinic

Abstract: Owing to the central role of apoptosis in many human diseases and the wide-spread application of apoptosis-based therapeutics, molecular imaging of apoptosis in clinical practice is of great interest for clinicians, and holds great promises. Based on the well-defined biochemical changes for apoptosis, a rich assortment of probes and approaches have been developed for molecular imaging of apoptosis with various imaging modalities. Among these imaging techniques, nuclear imaging (including single photon emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 95 publications
0
24
0
2
Order By: Relevance
“…Over the last four decades, molecular imaging has had a transformative effect on the way research is conducted in academia, industry and on how medical care is managed in the clinic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Of the modalities available to preclinical researchers and clinicians, the popularity of the nuclear medicine technique positron emission tomography (PET) has surged since it provides physiological data relating to disease pathophysiology, receptor expression levels, enzyme activity and cellular metabolism non-invasively and quantitatively [ 9 , 10 , 11 , 12 ]. PET imaging relies upon the unique decay characteristics of PET radionuclides, which decay by positron emission, and are chemically attached to ligands designed to probe biochemical phenomena in vivo [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, molecular imaging has had a transformative effect on the way research is conducted in academia, industry and on how medical care is managed in the clinic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Of the modalities available to preclinical researchers and clinicians, the popularity of the nuclear medicine technique positron emission tomography (PET) has surged since it provides physiological data relating to disease pathophysiology, receptor expression levels, enzyme activity and cellular metabolism non-invasively and quantitatively [ 9 , 10 , 11 , 12 ]. PET imaging relies upon the unique decay characteristics of PET radionuclides, which decay by positron emission, and are chemically attached to ligands designed to probe biochemical phenomena in vivo [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…99mTc labelled Annexin V has a high affinity for phosphatidylserine which is predominantly found on the plasma membrane of apoptotic cells. It has primarily been used in oncology but has also been studied in heart failure, cardiac transplant recipients and atherosclerosis [ 96 ]. In a small study of those undergoing carotid endarterectomy, uptake was shown to strongly correlate with high risk plaque characteristics (macrophage infiltration and intraplaque haemorrhage) suggesting a potential role for unstable plaque imaging [ 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dweck et al first demonstrated that coronary 18F-fluoride uptake was associated with cardiovascular risk, demonstrating significant associations between coronary arterial NaF uptake and prior coronary events, angina status and Framingham risk scores ( p =.016, p = 0.023 and p = 0.011, respectively) [ 96 ] This was supported by a study of 89 healthy adults, in whom 10-year risk scores for the development of cardiovascular disease were 2.4 times higher amongst adults in the highest quartile of coronary artery 18F-NaF uptake compared with those in the lowest (8.0 vs . 3.3%, p < 0.001) [ 107 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCD is a normal physiological process that plays an important role in growth and development. A large body of evidence has been established for animal PCD, while the molecular mechanisms of PCD remain to be explored in plants [30]. In this study, several microscopic methods were used to test for the occurrence of PCD during the arrest period of the stamen or carpel primordium in persimmon female or male buds, respectively.…”
Section: Discussionmentioning
confidence: 99%